2017
DOI: 10.1007/s10456-017-9551-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic approach for angiostatic therapy: promising combinations for cancer treatment

Abstract: Cancer cells are often dependent on epigenetic pathways for their survival. Consequently, drugs that target the epigenome, rather than the underlying DNA sequence, are currently attracting considerable attention. In recent years, the first epigenetic drugs have been approved for cancer chemotherapy, mainly for hematological applications. Limitations in single-drug efficacies have thus far limited their application in the treatment of solid tumors. Nevertheless, promising activity for these compounds has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 204 publications
0
17
0
Order By: Relevance
“…miR-126 is located in an intron of the EGFL7 (EGF-like domain multiple 7) gene, which is frequently silenced by methylation. As such, it suppression can be reversed by the application epigenetic therapeutics such as DNA methyltransferase and histone deacetylase (HDAC) inhibitors [103, 104], thereby increasing sensitivity to chemotherapy. In another study it was shown that entinostat, an HDAC inhibitor, increases the expression of miR-203 and miR-542-3p, which target surivin expression, responsible for paclitaxel resistance [105].…”
Section: Combination Of Mirna Therapy and Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…miR-126 is located in an intron of the EGFL7 (EGF-like domain multiple 7) gene, which is frequently silenced by methylation. As such, it suppression can be reversed by the application epigenetic therapeutics such as DNA methyltransferase and histone deacetylase (HDAC) inhibitors [103, 104], thereby increasing sensitivity to chemotherapy. In another study it was shown that entinostat, an HDAC inhibitor, increases the expression of miR-203 and miR-542-3p, which target surivin expression, responsible for paclitaxel resistance [105].…”
Section: Combination Of Mirna Therapy and Chemotherapymentioning
confidence: 99%
“…In another study it was shown that entinostat, an HDAC inhibitor, increases the expression of miR-203 and miR-542-3p, which target surivin expression, responsible for paclitaxel resistance [105]. Additional tumor-suppressive miRNAs silenced by epigenetic events have recently been identified [106], providing opportunities in combining epigenetic therapeutics for miRNA regulation in combination with other agents [104]. …”
Section: Combination Of Mirna Therapy and Chemotherapymentioning
confidence: 99%
“…[117] Diverse proteins are involved in maintaining epigenetic regulation by placing, removing, moving, or binding histone modifications, that is, acetylation, methylation, and other epigenetic residues. [119] In recent years, histone methylation and deacetylation inhibitors have been clinically evaluated for colorectal or gastrointestinal diseases as well as other cancer types and, notably, have proven to be effective in phase I and II trials. [119] In recent years, histone methylation and deacetylation inhibitors have been clinically evaluated for colorectal or gastrointestinal diseases as well as other cancer types and, notably, have proven to be effective in phase I and II trials.…”
Section: Rapta-c and Histone-targeting Drugsmentioning
confidence: 99%
“…Diverse proteins are involved in maintaining epigenetic regulation by placing, removing, moving, or binding histone modifications, that is, acetylation, methylation, and other epigenetic residues . These proteins can be targeted by drugs and RAPTA‐C appears to correspond to this group of epigenome and histone‐modifying drugs, binding directly with the histone proteins in chromatin at the same site that certain chromatin factors bind, thus inhibiting their function …”
Section: Rapta‐c and Histone‐targeting Drugsmentioning
confidence: 99%
“…A promising effort in the development of anticancer drugs is the approach of targeting epigenetics of cancer. Berndsen et al [9] examine the role of epigenetic drugs as angiostatics, as well as the application of epigenetic drugs in combination with regular angiostatic-targeted agents. The authors present an extensive literature review of various classes of epigenetic compounds, both clinically approved and experimental compounds that are paving the way to effective combination strategies.…”
mentioning
confidence: 99%